First Organocatalytic Asymmetric Synthesis of 1-Benzamido-1,4-Dihydropyridine Derivatives - Auria-Luna, Fernando (Molecules, 2018)
Preliminary results concerning the first asymmetric synthesis of highly functionalized 1-benzamido-1,4-dihydropyridine derivatives via the reaction of hydrazones with alkylidenemalononitriles in the presence of β-isocupreidine catalyst are reported. The moderate, but promising, enantioselectivity observed (40–54% ee), opens the door to a new area of research for the asymmetric construction of new chiral 1,4-dihydropyridine derivatives, whose enantioselective catalytic preparation are still very limited. Moreover, the use of hydrazones for the enantioselective construction of chiral 1,4-dihydropyridines has been overlooked in the literature so far. Therefore, our research represents a pivotal example in this field which remains still unexplored.